Pengaruh Shift Kerja dan Beban Kerja Terhadap Kinerja Perawat Pada Moslem Baby Day Care di Timoho Yogyakarta (Studi Pada Moslem Baby Day Care) - Bunga Putri Arini (Akmenika: Jurnal Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of work shifts and workload on the performance of nurses on Musoh Baby Day Care in Timoho Yogyakarta. Samples taken were all Moslem Baby Day Care nurses in Timoho Yogyakarta, amounting to 38 people with population sampling techniques. The analysis technique uses multiple regression analysis. This study found that (1)work shifts had a significant effect on the performance of Moslem Baby Day Care nurses in Timoho, Yogyakarta. (2) Workload has a significant effect on the performance of Moslem Baby Day Care nurses in Timoho, Yogyakarta. (3) Work shift has a significant effect on the workload of Moslem Baby Day Care nurses in Timoho, Yogyakarta.Â Keyword: work shift, performance, baby day care